The Hukum Kanun Pahang: A Forgotten Malay-Islamic Constitutional and Maritime Legacy - Tunku Azizah Mahmood Iskandar, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2026)
This study reconstructs Pahang’s historical and intellectual identity as a sovereign Malay-Islamic civilisation whose governance was founded upon law rather than conquest. At its centre stands the Hukum Kanun Pahang (HKP), compiled and codified during the reign of Sultan ʿAbdul Ghaffar Muhyiddin Shah ibni Sultan Abdul Qadir Muhyiddin Shah (1592–1614), which is argued here to constitute the embryonic form of a Malay-Islamic constitution. Long before the emergence of Western constitutional theory, the Malay world had already articulated a written constitutional order grounded in sharī’ah, ‘adat, justice, and accountability to Allah. The HKP unified terrestrial and maritime sovereignty, extending law from palace to port, from river to sea, and codifying the duties of ruler and subject, judicial procedure, trade ethics, maritime order, taxation, and moral conduct. Far from representing primitive law, the HKP reflects proto-constitutional thought and the earliest living expression of Malay constitutionalism, principles that later found continuity in the Undang-Undang Tubuh Kerajaan Pahang (UTKP). Through socio-historical approach this study re-centres Pahang as a great maritime civilisation, a key site of Islamic constitutional development in Southeast Asia and reclaims the HKP as one of the world’s earliest comprehensive constitutional texts.